Effects of staining and polishing on different types of enamel surface sealants - Corcodel, Nicoleta; Hassel, Alexander J.; Şen, Sinan; Saure, Daniel; Rammelsberg, Peter; Lux, Christopher J.; Zingler, Sebastian (Journal of esthetic and restorative dentistry, 2018)
Objective To assess surface discoloration of four enamel sealants based on different chemical compositions after exposure to artificial aging and staining solutions. Furthermore, their cleanability after polishing will be evaluated. Materials and Methods Selected sealants were a composite resin-based sealant with fillers (Pro Seal), a composite resin-based sealant without fillers (Light BondSealant), a resin-modified glass ionomer-based sealant (ClinproXT Varnish) and a silicon-based sealant (Protecto). Natural teeth served as medium. Immersion solutions were water, juice, tea, and turmeric. In a standardized setting, all samples were measured seven times with a spectroradiometer (Photoresearch PR670) at baseline, after thermocycling; 7 days; 2 and 4 weeks of immersion; and after finally polishing. Results Thermocycling had no significant effect on color stability. After exposure to staining solutions, all sealed surfaces showed significant color changes. Color change predominately occurred for all sealants in the first week of staining (P ≤ .01). Best resistance to staining decreased as follows: Protecto > Light Bond Sealant > ProSeal > Clinpro XT Varnish. Surface cleaning by polishing significantly reduced the color change. Conclusion Sealed enamel surfaces are prone to discoloration, which is most prominent in filled composite and glass-ionomer-based sealants. Staining can be reduced by polishing; however, in this in vitro setting the original color could not be restored. Clinical Significance Enamel sealants might exert adverse effects in terms of discoloration. This should be taken into consideration by clinicians and patients, particularly when sealants are applied in esthetically critical areas.